CLINICO-PHYSIOLOGICAL CHANGES ON EPIDURAL ADMINISTRATION OF ROPIVACAINE ALONE AND IN COMBINATION WITH DEXMEDETOMIDINE IN BUFFALO CALVES - Kamble, S; Pandey, SS; Shukla, BP; Jain, R (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present study was conducted on 12 healthy buffalo calves of 6-12 months of age. The objective of the study was to investigate the clinico-physiological changes after administration of ropivacaine alone and in combination with dexmedetomidine as an epidural analgesia. Temperature and respiration showed non significant changes in both the groups, there was non significant change in heart rate in group II whereas in ropivacaine - dexmedetomidine group significant changes were observed. The onset and duration of analgesia was early and prolonged in ropivacaine dexmedetomidine combination as compared to ropivacaine group. Minimal ataxia was seen in group administered with ropivacaine alone.
Keywords: Clinico-physiological changes; Epidural Ropivacaine; Dexmedetomidine